Comprehensive assessment of technical condition of vehicles during operation based on Harrington’s desirability function - Aulin, Viktor; Rogovskii, Ivan; Lyashuk, Oleh; Titova, Liudmyla; Hrynkiv, Andrii; Mironov, Dmytro; Volianskyi, Mykhailo; Rogatynskyi, Roman; Solomka, Oleksiy; Lysenko, Serhii (Eastern-European Journal of Enterprise Technologies, 2024)
The object of research is the process of changing the technical condition of vehicles during their operation. The study solved the problem of comprehensive evaluation of change in the technical condition based on Harrington’s desirability function. The essence of the results is as follows. A scale of desirability was built and a set of criteria for assessing the technical condition of vehicles was clarified. A general desirability index is proposed as a convolution of partial Harrington desirability functions. When solving the investigated problem, the characteristics and properties of the partial and generalized Harrington’s desirability function and their graphical representation were taken into account. Using an example of the technical condition of the chassis and braking system of vehicles, a set of controlled parameters was formed. Based on the values of the controlled parameters, the regression equation of the partial Harrington desirability functions was obtained. The value of the weighting coefficients of each of the criteria was determined and the generalized desirability function was calculated. As a result of the study, it was established that if the generalized criterion of desirability is D<0.37, then individual nodes, systems, and units of the vehicle are in a pre-accident condition, if 0.37£D£0.63 – in a satisfactory condition, and if D>0.63 – in a good condition and cannot be the cause of a traffic accident. An applied aspect of the results is the implementation of the technique of comprehensive assessment of the technical condition of the vehicle. This causes an increase in the productivity of the expert (specialist), will shorten the period of the auto technical examination, and improve its quality. The results could be used by insurance companies and investigators, investigators and judges when considering traffic accidents